JUSTICIAL PRESS IN CHILE? THE TABLOIDES OF SANTIAGO AND THE INVESTIGATING COMMISSION ON THE DISSEMINATION OF PERONISM IN CHILEAN JOURNALISM, 1952-1956 - Acuña, Pedro Ignacio (Revista de Historia Social y de las Mentalidades, 2022)
This article examines the journalistic language of the tabloids Las Noticias Gráficas and Última Hora in relation to the figure of Argentine President Juan Perón (1946-1955). Unlike the rest of the Chilean press, both evening papers published in Santiago displayed an articulate defense of the Argentine regime, arousing suspicions among Chilean political circles. The Chilean Congress formed a Special Investigating Commission on Peronist Activities in Chile to investigate the infiltration of Peronism in different Chilean institutions, including political parties, armed forces, trade unions, and journalistic media. The Commission elaborated a detailed report that accredited strong connections between Argentine state agencies and a group of Chilean journalists willing to publish favorable news about the Peronist regime in Argentina.